Prevalence and genetic diversity of HBV and HDV strains circulationg in Niger and in Mauritania - (:unkn) unknown (My University, 2012)
Chronic carriage of hepatitis B virus (HBV) in Africa is very high, reaching as much as 30% in some areas. According to WHO, about 400 million people suffering from chronic HBV infection, 70 to 140,000,000 live in Africa with an annual death rate of about 250 000 cases per year. Data on concomitant infection by the hepatitis D virus (HDV), satellite of HBV, are rare because few studies have been conducted in Africa. Despite this high prevalence, data on the molecular characterization of HBV and HDV strains are limited or nonexistent in most countries of Sub-Saharan Africa and particularly in the Saharan region, a vast multi-ethnic area, crossing and mixing of populations. In this study, we wanted to determine the prevalence and molecular epidemiology of HBV and HDV strains circulating in the Saharan region (Niger and Mauritania). First, we studied a cohort of HBsAg positive blood donors in Niger. We found that 80% of the strains tested belonged to genotype E. In addition, we identified and characterized a novel recombinant HBV/D-HBV/E, which represents nearly 20% of the strains studied. The breakpoints were located in "hot spots" of recombination regions involved in the events of integration of HBV genome. Extensive phylogenetic analyzes have allowed us to classify it as a new subgenotype. We proposed HBV/D8. We then, in collaboration with local teams, studied the genetic HBV diversity in Mauritania, a neighboring country of Niger, in various representative groups of the population: pregnant women (n = 1020), consulting patients (n = 954) blood donors (n = 11,110) and patients treated for chronic HBV infection (n = 300). The carrier rate of HBsAg was 11 to 18% depending on the population studied, classifying Mauritania as high HBV endemic country. Exposure to HBV was associated in multivariate analysis to the level of education, ethnicity, history of transfusion and the profession in pregnant women, and in consulting patients, to male gender. At the mo
Keywords: African Research